2018
DOI: 10.1556/0088.2018.00014
|View full text |Cite
|
Sign up to set email alerts
|

Antropogén hatások becslése hazai talajokban felszínborítási adatok és WRB diagnosztika alapján

Abstract: A WRB diagnosztikai elemeit és a felszínborítási adatokat kombinálva a talajokat ért antropogén hatás mértéke szerint négy csoportot alkottunk: 1. nincs talaj, 2. antropogén eredetű talaj, 3. természetes talaj, de lényeges antropogén bélyegekkel, illetve 4. természetes talaj. A négy csoport valamelyikéhez egyértelműen hozzárendelhető a felszínborítási osztályok mindegyike. Az általunk kidolgozott módszer segítségével értékeltük Magyarország talajtakarójának természetességét. Az ország területének 2%-án nem szá… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…The The rate of soil erosion (Kerényi, 1991;Kerényi and Martonné, 1994;Novák, 2013) based on Hungarian Soil Classification System (Murányi et al, 1989;Novák, 2013 differences observed can also be explained by the fact that our designated soil profiles provide data around a given point, and do not examine individual factors based on complete area coverage. We agree that land cover and soil condition (soil erosion) can be good indicators for examining the degree of anthropogenic transformation (Novák and Incze, 2018;Novák et al, 2019).…”
Section: Discussionsupporting
confidence: 67%
“…The The rate of soil erosion (Kerényi, 1991;Kerényi and Martonné, 1994;Novák, 2013) based on Hungarian Soil Classification System (Murányi et al, 1989;Novák, 2013 differences observed can also be explained by the fact that our designated soil profiles provide data around a given point, and do not examine individual factors based on complete area coverage. We agree that land cover and soil condition (soil erosion) can be good indicators for examining the degree of anthropogenic transformation (Novák and Incze, 2018;Novák et al, 2019).…”
Section: Discussionsupporting
confidence: 67%